Long non-coding RNA NEAT1 can predict various malignant tumour lympha node metastasis: a meta-analysis - Lei Zhang; Zhe Zhang; Zhenglun Yu (Artificial Cells, Nanomedicine, and Biotechnology)
It has been found in several studies and research that the long non-coding RNA (Inc RNA) NEAT1 plays an important role in the development and succession in various malignant tumour. The development and metastasis of tumour mainly happen through lymph node. The purpose of this research is to explore the value of lymph node metastasis (LNM) in cancer. We have collected all the concerned studies about NEAT1 and researched the relationship between NEAT1 and lymph node metastasis. We have searched the studies by seeking database PubMed, Web of Science, and China National Knowledge Infrastructure (up to 10 January 2019), as well as a total of 821 patients from eight studies topics and made accordingly meta-analysis. By analyzing the data, we have found that the result is the high expression of NEAT1 associate with the metastasis of lymph node in different malignant tumours. The high level of NEAT1 expression can predict the metastasis of lymph node (OR = 3.36, 95% CI = 1.66–6.77, p = .000) and it is a molecular marker of positive lymph node for treatment.